Rare bird documentation form for Peregrine Falcon at Sand Point in Hawkeye Wildlife Area, 1985 - Knight, Calvin A.et al (1985)
Rare bird documentation form for a Peregrine Falcon at Sand Point in Hawkeye Wildlife Area in Johnson County, IA on May 7, 1985. Epson - sheet feed